2004
DOI: 10.1152/jn.00487.2003
|View full text |Cite
|
Sign up to set email alerts
|

Is Spontaneous High-Voltage Rhythmic Spike Discharge in Long Evans Rats an Absence-Like Seizure Activity?

Abstract: Shaw, Fu-Zen. Is spontaneous high-voltage rhythmic spike discharge in Long Evans rats an absence-like seizure activity? J Neurophysiol 91: 63-77, 2004. First published June 25, 2003 10.1152/jn.00487.2003. A distinct high-voltage rhythmic spike (HVRS) discharge characterized by a barrage of negative spikes oscillating at 5-12 Hz was observed in chronically implanted Long Evans rats. Spontaneous HVRS discharges were exhibited in 90% of 40 Long Evans rats and occurred during sudden arrest of ongoing behavior (im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
111
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(136 citation statements)
references
References 58 publications
24
111
1
Order By: Relevance
“…HVS activity in the neocortex of Long-Evan rats has long been known to be associated with vibrissal and facial muscle movements (Vanderwolf, 1975;Semba et al, 1980;Shaw, 2004). More recent studies indicated that HVS involved thalamocortical structures (Buzsaki, 1991;Kandel and Buzsáki, 1997), and was suppressed by anti-absence anticonvulsants, such as ethosuximide and valproate (Shaw, 2007), similar to SWDs in spontaneous genetic models of absence seizures (Coenen et al, 1992), or PDs induced by GBL (Snead et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HVS activity in the neocortex of Long-Evan rats has long been known to be associated with vibrissal and facial muscle movements (Vanderwolf, 1975;Semba et al, 1980;Shaw, 2004). More recent studies indicated that HVS involved thalamocortical structures (Buzsaki, 1991;Kandel and Buzsáki, 1997), and was suppressed by anti-absence anticonvulsants, such as ethosuximide and valproate (Shaw, 2007), similar to SWDs in spontaneous genetic models of absence seizures (Coenen et al, 1992), or PDs induced by GBL (Snead et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In many rats, occasional, high-amplitude 6-9 Hz activity called high-voltage spindles (HVS) could appear in the neocortex and thalamus during baseline immobility ( Fig. 1A, B; Vanderwolf, 1975;Semba et al, 1980;Buzsáki, 1991;Shaw, 2004). An episode of HVS consisted of a burst of 6-9 Hz spike-and-wave discharges that waxed and waned over 1-4 s duration (Fig.…”
Section: Change Of Local Field Potentials During Gbl-induced Seizuresmentioning
confidence: 99%
“…1b, d and f), amplitude 0.2-1.0/0.3-1.0/0.1-2.0 mV, duration 1-30/5-60/1-40 s (Akman et al, 2010;Coenen and Van Luijtelaar, 2003;Depaulis and Van Luijtelaar, 2005;Polack and Charpier, 2006;Shaw, 2004). The number of SWDs may vary between 15-40/20-80/6-90 (per hour) in WAG/Rij rats, GAERS rats and Long Evans rats depending on the time of the day and age of animals (Akman et al, 2010;Coenen and Van Luijtelaar, 2003;Depaulis and Van Luijtelaar, 2005;Polack and Charpier, 2006;Shaw, 2004). To avoid the modulatory effect of age and sleep-wake cycle on SWD number, electrophysiological recordings were carry out on eight months old animals (±1 week) between 4.00 PM and 8.00 PM.…”
Section: Eeg Recording and Swd Scoringmentioning
confidence: 97%
“…injections were not included into the analysis. In relation to individually different SWD number and duration (Kovács et al, 2006;Polack and Charpier, 2006;Shaw, 2004), the changes in SWD numbers and duration were expressed in percentage of average control measures (three-day Table 1 The treatment protocol of the twelve animal groups carried out WAG/Rij rats, GAERS rats and Long Evans rats. Abbreviations: IND, indomethacin; i.p., intraperitoneal; LPS, lipopolysaccharide; PTC day, post-treatment control day.…”
Section: Eeg Recording and Swd Scoringmentioning
confidence: 99%
See 1 more Smart Citation